Bezpieczeństwo zdrowotne obywateli w państwowym systemie bezpieczeństwa wewnętrznego - Paplicki, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Security constitutes an individual as well as social groups’ chief need. Therefore, it establishes both the state and international systems. Its lack causes the sense of anxiety and insecurity.Protection of life, meant as abiological existence of aman, is an obvious assumption of each and every civilized country. The state itself is astructure designed to last and develop on the basis of living society.Consequently, life protection is thus inscribed in the very essence of the state. It is only the state along with its administration that has an appropriate structure and power in order to provide security in the broadest sense.For the purpose of this study it was assumed that health safety is considered as the centrality of actions taken by the government administration including all the subordinate departments in order to protect life and health.The life protection-related laws have been analyzed and checked whether the authorities, committed to support health, fulfill their duties. The conclusions can raise citizens’ concerns about their health security.
Keywords: bezpieczeństwo zdrowotne; państwowy system bezpieczeństwa wewnętrznego; konstytucja 1997; publiczne prawo podmiotowe; ochrona życia i zdrowia